Space-time relationship of Meloidogyne and Pratylenchus with biometric, nutritional and enzymatic attributes of sugarcane - Silva, Luana Maria Alves da; Pedrosa, Elvira Maria Regis; Vicente, Thais Fernanda da Silva; Leitão, Diego Arruda Huggins de Sá; Carvalho, Rezanio Martins; Santos, Ananda Rosa Beserra; Simeão, Marcelo (Research, Society and Development, 2023)
Two field experiments were carried out in the city of Camutanga, Pernambuco, Brazil, to evaluate relationships between the plant-parasitic nematodes Meloidogyne and Pratylenchus and plant biometric, nutritional and antioxidant enzymes attributes of sugarcane (plant cane and ratoon). Evaluations, carried out at 6, 9, and 12 months after planting (Area 1) or ratoon cutting (Area 2), based on the endoparasites population level in root, stalk height, stalk diameter, number of stalks and tillers, superoxide dismutase and ascorbate peroxidase activity. Data were submitted to descriptive and geostatistical analysis, generating isolines maps by means of theoretical semivariograms adjusted to the data semivariance. The spherical and exponential models were adjusted for most variables evaluated. In Area 1, the spatial-temporal distribution patterns of Meloidogyne and Pratylenchus differed over time, running to a more homogeneous trend along the time. The ratoon development in Area 2 was affected by sites of high population density of Pratylenchus, matching with the lower potassium and magnesium levels.